Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Adira Dinamika Multi Finance Cabang Margonda Depok - Annisa Nabila (Lembaga Pengembangan Kinerja Dosen, 2023)
Employee performance is crucial to the success of an organization. To improve and optimize performance, factors such as work motivation and work environment play a crucial role. The study used a total sampling technique or a saturated sample, with a total sample of 38 people from a total population of 60 people. These data were analyzed by the authors using validity tests, reliability tests, classical assumption tests, and hypothesis tests using the Statistical Product and Service Solutions (SPSS) application program, Version 22. Based on the results of the research, it is partially and simultaneously known that motivation and working environment have a positive and significant impact on the performance of employees at PT Adira Dinamika Multi Finance Branch Margonda Depok.